Does urbanization lead to more direct and indirect household carbon dioxide emissions? Evidence from China during 1996–2012. (1st September 2015) - Li, Yanmei; Zhao, Rui; Liu, Tianshu; Zhao, Jianfeng
Abstract: China is experiencing a stage of rapid urban development. The energy consumption and related carbon dioxide emissions of households continue to increase. This paper calculates direct and indirect carbon dioxide emissions of households based on the input–output method in China from 1996 to 2012. The results reveal that there were more total carbon dioxide emissions from urban households than from rural households, far more indirect emissions from urban households than from rural households, slightly more direct emissions from urban households than from rural households, and differences in direct carbon dioxide emissions from various fuels and in indirect emissions from various sectors between urban and rural households. To examine the causal relationship between urbanization and the carbon dioxide emissions of households, cointegration and Granger causality tests are applied. A unidirectional causal relation was found running from urbanization to both direct and indirect household carbon dioxide emissions, and the direct and indirect carbon dioxide emissions of households would increase 2.9% and 1.1%, respectively, for every increase of one percent in urbanization. We discuss the reasons of why the development of urbanization will lead to more household direct and indirect carbon dioxide emissions, and suggest certain policy implications for urbanization and carbon dioxide emissions based on the results of this study. Highlights: Direct and indirect carbon emissions of households are calculated. Differences in carbon emissions between urban and rural households are identified. A unidirectional causal relation was found running from urbanization to emissions. Reasons of why urbanization leads to more household carbon emissions are discussed. Policy implications for urbanization and carbon emissions are suggested.